Tata Kelola Kompetensi Guru - Heryati, Neneng (Journal of Governance and Administrative Reform, 2022)
Abstract The world is changing and developing so fast as technology changes and information becomes increasingly sophisticated. The changing times must be balanced with the development of education in a more advanced direction. Kemdikbud as a government institution has duties and functions in providing public services in the field of education. The Ministry of Education and Culture must have good teacher governance. Efforts were made for teacher governance. Laws related to teachers were issued, one of which was the 2005 Teacher and Lecturer Law. Development of a teacher management information system. Provision of tuition assistance funds for teachers to improve academic qualifications to meet the minimum standard of S1. Teacher professional education organized by universities to obtain educator certificates. Continuing Professional Development (CPD) program so that teachers maintain and develop their competence. Until now the quality of teachers is still low. The main problems for teachers are sub-standard competence, academic qualifications that do not meet the requirements, and teachers who are not certified educators. Identification of factors that influence teacher competence is very important as a reference for making teacher governance policy decisions. Several factors influence teacher competency. The Ministry of Education and Culture seeks to realize better teacher competency governance. Ministry of Education and Culture is dynamically changing and how it always develops knowledge to solve problems and make innovations. The management of teacher competence is carried out in collaboration with the involvement of other actors such as district/city/provincial education offices, universities and related ministries/institutions.   Abstrak Dunia berubah dan berkembang begitu cepat seiring perubahan teknologi dan informasi yang semakin canggih. Perubahan zaman harus diimbangi dengan perkembangan pendidikan ke arah yang lebih maju. Kemdikbud sebagai lembaga pemerintah mempunyai tugas dan fungsi dalam memberikan layanan publik dalam bidang Pendidikan. Kemdikbud harus mempunyai tata kelola guru yang baik. Upaya-upaya dilakukan untuk tata kelola guru. Diterbitkan perundang-undangan terkait guru, salah satunya UU Guru dan Dosen tahun 2005. Pengembangan sistem informasi manajemen guru. Penyediaan dana bantuan biaya pendidikan bagi guru untuk meningkatkan kualifikasi akademik untuk memenuhi standar minimum S1. Pendidikan profesi guru yang diselenggarakan oleh universitas untuk mendapatkan sertifikat pendidik. Program Continuing Profesional Development (CPD) agar guru mempertahankan dan mengembangkan kompetensinya. Hingga saat ini kualitas guru masih rendah. Masalah utama guru, yaitu kompetensi di bawah standar, kualifikasi akademik yang tidak memenuhi syarat, dan guru yang belum bersertifikat pendidik. Identifikasi faktor yang mempengaruhi kompetensi guru sangat penting sebagai acuan pengambilan keputusan kebijakan tata kelola guru. Beberapa faktor mempengaruhi kompetensi guru. Kemdikbud berupaya mewujudkan tata kelola kompetensi guru yang lebih baik. Kemdikbud secara dinamis berubah dan bagaimana selalu mengembangkan pengetahuan untuk menyelesaikan masalah dan membuat inovasi. Tata kelola kompetensi guru dilakukan dengan kerjasama pelibatan aktor lain seperti dinas pendidikan kabupaten/kota/ provinsi, universitas dan kementerian/ lembaga terkait.